The concept, dimensions, and measurement of innovative competitive behavior of Chinese scientific and technological personnel - Li, Ping; Fang, Weihua; Hou, Guannan; Li, Rui (Frontiers in Psychology, 2025)
IntroductionWhile competitive behavior in innovation activities is increasingly prevalent in practice and actively promoted by policymakers, it remains an under explored area in academic research. To bridge this gap, we introduce the concept of “innovative competitive behavior,” providing a conceptual definition and clarifying its theoretical boundaries, rooted in social comparison theory from psychology.MethodsA mixed-methods approach was employed to systematically examine this construct. First, a qualitative study guided by grounded theory was conducted to explore the core dimensions of the construct. Subsequently, a quantitative phase involved the development and validation of a psychological scale through questionnaire surveys and factor analysis.ResultsThe qualitative phase identified two core dimensions: competitive behavior in innovation input (including acquiring, allocating, and utilizing resources) and competitive behavior in innovation output (involving competition in the quantity, quality, and outcomes of innovation). These dimensions form the foundation of the proposed Four-Degree Diamond Model of innovative competitive behavior. In the quantitative phase, a 13-item Innovative Competitive Behavior Scale was developed and validated, demonstrating satisfactory reliability and validity.DiscussionBy integrating innovation theory and competition theory at the micro level, this research contributes to the emerging literature on individual-level innovative competition and establishes a theoretical foundation for future studies. These findings offer a roadmap for policymakers and corporate managers to effectively incentivize scientific and technological personnel, thereby enhancing innovation performance through innovative competition.